Penerapan Model Pembelajaran PBL (Problem Based Learning) Berbasis CRT (Culturally Responship Teaching) Untuk Meningkatkan Motivasi Belajar Siswa SMAN 6 Palu - Nita Diniati, Baiq; L. Tangge; Nurhaida (Universitas Cokroaminoto Palopo, 2025)
Learning will be more meaningful if there is encouragement or a desire to learn. This encouragement is what is called learning motivation. To build learning motivation, efforts were made, including the implementation of the Problem-Based Learning (PBL) model and the Culture-Based Approach (CRT). The purpose of this study was to improve the learning motivation of tenth-grade Anggrek students at SMAN 6 Palu, Central Sulawesi, through the implementation of the PBL model and the CRT approach. This study used classroom action research (CAR). The research design adopted the Kemmis & MC Taggart design. The study was conducted in two cycles, each consisting of planning, implementation, observation, and reflection. Data were obtained through questionnaires administered to students in cycles 1 and 2. Data analysis was conducted descriptively. Based on the data analysis, the results showed an average increase in student learning motivation of 74 in cycle 1, which is considered quite good, and 80 in cycle 2, which is considered good. This proves that there is an increase in student learning of the Problem Based Learning (PBL) on cultural approach (CRT).